Association between Aqueous Cytokines and Diabetic Retinopathy Stage - Hailiang Wu; De-Kuang Hwang; Xudong Song; Yong Tao (Journal of Ophthalmology)
Purpose. To measure the concentrations of various cytokines in the aqueous humor from patients with different stages of diabetic retinopathy. Methods. All selected cataract patients were categorized into 4 groups: the control group (patients without diabetes), nonretinopathy (NDR) group (diabetic patients without retinopathy), nonproliferative diabetic retinopathy (NPDR) group, and proliferative diabetic retinopathy (PDR) group. The aqueous concentrations of interleukin- (IL-) 1β, IL-2, IL-4, IL-5, IL-6, IL-10, interferon-γ, tumor necrosis factor-α, and vascular endothelial growth factor (VEGF) from patients were measured using the cytometric bead array technique. Results. In this study, 10, 22, 15, and 14 patients were included in the control, NDR, NPDR, and PDR groups, respectively. No difference was observed in the aqueous concentrations of all cytokines between the control group and the NDR group. By contrast, comparison of these groups revealed that the aqueous concentrations of most inflammatory cytokines were significantly higher in the PDR and NPDR groups. In addition, the concentrations of IL-2, IL-5, and VEGF were higher in the PDR group than those in the NPDR group. Conclusions. Aqueous concentrations of various cytokines increased with the severity of patients’ diabetic retinopathy. This finding implies that these cytokines might play a role in the progression of diabetic retinopathy.